Heptavalent ARC-transitive cayley graphs on frobenius groups with soluble vertex stabilizer - Liu, Hailin (Utilitas Mathematica, 2019)
A Cayley graph Γ is said to be arc-transitive if its full automorphism group Autr is transitive on the arc set of Γ In this paper, we give a characterization of heptavalent arc-transitive Cayley graphs on a class of Frobenius groups with soluble vertex stabilizer. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.